A loucura histérica: da mostração do corpo em sofrimento à elaboração na palavra - Apparecido, Patrícia Bouças (2018)
Based on the clinical case, this paper articulates the concept of hysterical madness as a condition that is present in hysterical neurosis and that has radical and severe manifestations, often similar to a psychotic outbreak due to the proportion of its dissociative manifestations and its excessive crises that look like a rupture, as in psychosis. I here present the subject's response to anguish, especially in passage to the act and acting-out, recurring in the clinical case analyzed. I approach the discursive structure of hysteria and hysterical madness, both of them associated to a complaint of father's inadequacy and an insistent demand for the Other to supply to the overflowing inward. I also mention the differences in paternal function in psychosis and in hysteria, the constitution of the subject – based on The Time of Oedipus –, and Lacan’s Mirror Stage. Finally, from the theoretical-clinical articulation, I develop the treatment conduction, from transference management to possible subjective constructions